Identifying Typologies of Persons Who Died by Suicide: Characterizing Suicide in Victoria, Australia. Issue 1 (2nd January 2020) - Clapperton, Angela; Bugeja, Lyndal; Newstead, Stuart; Pirkis, Jane
Abstract : The objective of the study was to determine whether people who died by suicide form groups based on demographic, psychosocial, mental and physical health factors and exposure to stressors. A retrospective case series review of 2, 839 individuals who died by suicide in Victoria, Australia over the period 2009–2013 was conducted. A two-stage cluster analysis was performed. Diagnosis of mental illness was present in 52% of cases and initial cluster analysis determined two groups with the main predictor of group membership being the presence of diagnosed mental illness. Further analysis identified four subgroups within the mental illness group and two within the non-mental illness group. The study demonstrates that suicide does not always occur in the context of mental illness; people who die by suicide cannot be considered a homogenous group.